ANALISIS EFEKTIVITAS PEMBIAYAAN MURABAHAH DALAM MENINGKATKAN PROFITABILITAS BANK SYARIAH DI INDONESIA - Dinda Nurayuni Humaira; Fadillah Syafitri; Syarifah Hanum Tumangger; Muhammad Ikhsan Harahap (CV. Barokah Publsiher, 2025)
Murabahah financing is the most dominant financing product in the Islamic banking portfolio and serves as a stable source of income for banks. However, the increase in murabahah financing volume does not always correspond with higher profitability. This study aims to analyze the effectiveness of murabahah financing in improving the profitability of Islamic banks in Indonesia through a literature review approach. The data used include murabahah financing trends and the Return on Assets (ROA) ratio based on the 2020–2024 Islamic Banking Statistics published by the Financial Services Authority (OJK), along with 20 relevant national scientific articles published between 2022 and 2025. The results show that financing effectiveness acts as the key mediating factor linking murabahah financing to profitability. Murabahah contributes positively to profitability only when financing effectiveness is high, indicated by strong risk management, operational efficiency, digitalization, and payment smoothness. Conversely, when effectiveness is low, financing risks increase and profitability decreases despite higher financing volumes. This study recommends strengthening digitalization, improving human resource competence, and enhancing risk management to optimize the value of murabahah financing for Islamic banks. Future research is expected to employ quantitative methods to empirically test the relationships among variables.